Spatial Thinking Analysis of Geographic Students Based on Lesson Study for Learning Community (Lslc) in Geographic Learning - Rahmanelli, Rahmanelli; Prarikeslan, Widya (Sumatra Journal of Disaster, Geography and Geography Education, 2019)
Spatial thinking in geography learning is very important to explain phenomena, find meaning, answers, and solutions about shape, size, orientation, location, direction, objects in certain spaces on the earth's surface. Therefore, geography students must be able to solve problems in their environment through spatial thinking.